Advanced Land Warfare Tactics and Operations - Weissmann, Mikael; Nilsson, Niklas (Oxford University Press, 2023)
International politics have become ever more volatile over the last decade, increasing the risk of large-scale military violence. Yet the precise character of future war will depend on a range of factors that relate to adversaries, allies, technology, geographical scope and multiple domains of warfighting. Few would question that land forces will be important also in the foreseeable future. However, given that the battlefield is in a state of transformation, so is the mission, purpose and utilization of land forces. Indeed, the future conduct of land warfare is subjected to serious and important questions in the face of large and complex challenges and security threats. This volume explores the evolving role of land forces, paying particular attention to the changes that have taken place in the art of commanding and executing combat and the role of rapid technological innovation and information dissemination in shaping warfare. It provides insights into key contemporary developments in land warfare, and presents case studies on land tactics and operations in different national contexts. The volume aims to draw on the best of theory, practice, and professional experience, featuring chapters written by leading international scholars and practitioners. Relating to the realities of the modern battlefield, the volume addresses a number of critical questions about land tactics and operations, combining a conceptual basis with empirical examples of tactical thinking and practice and emphasising the importance of understanding the perspectives of various national armies, in order to provide a current understanding of the central issues of land warfare.